Fibular tendon graft as an alternative for anterior cruciate ligament reconstruction of the knee: Case report: Fibular tendon graft in ACL - Anna Beatriz L. Silva; Anna Luísa L. Milani; Beatriz R. Teixeira; Izadora O. Leite; Giovana A. Paranhos; Layla M. Rios; Andrei M. V. Trindade; José Augusto Souza Neto; Phablio José Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2025)
<!--StartFragment--> Background: Anterior cruciate ligament (ACL) injury significantly compromises knee stability, especially during sports activities. Surgical reconstruction using tendon grafts is the standard treatment, with autografts (patellar, hamstring, quadriceps, and peroneus longus tendons) being the most commonly used. The patellar tendon is considered the gold standard, but its donor site morbidity has encouraged the search for alternatives such as the peroneus longus tendon. Objective: To report the use of the peroneus longus tendon as a graft in ACL reconstruction, highlighting its feasibility as an alternative to conventional techniques and the observed clinical outcomes. Method: The study involved a 35-year-old female patient with a complete right ACL tear following a sprain during physical activity. Reconstruction was initially indicated using hamstring tendons (semitendinosus and gracilis), but intraoperative evaluation revealed insufficient thickness and length. The ipsilateral peroneus longus tendon was then harvested as a complementary graft. Results: The patient showed favorable postoperative evolution, with proper healing and initiation of functional rehabilitation. Graft selection for ACL reconstruction depends on factors such as stability, muscle strength, complications, and functional goals. The peroneus longus tendon offers advantages such as suitable diameter, tensile strength, lower morbidity, and a safe harvesting technique, making it a promising option when conventional grafts are inadequate. Studies indicate lower revision rates when graft diameter is sufficient, reinforcing its applicability. Conclusion: The peroneus longus tendon proved to be an effective and safe alternative graft for ACL reconstruction, especially in cases where hamstring tendons are insufficient. It demonstrated good functional outcomes, strength, and low donor site morbidity.